Total ankle arthroplasty and deformity - is there a limit? - Bergman, Rachel; Umrethiya, Viren; R. Kadakia, Anish (Journal of the Foot & Ankle, 2026)
Total ankle arthroplasty (TAA) has undergone a paradigm shift over the past decades, moving from being regarded as inferior to arthrodesis to becoming a preferred option for many patients with end-stage ankle arthritis. Advances in implant design, better understanding of biomechanics, and refinement of surgical techniques have expanded its indications and outcomes. Compared with arthrodesis, TAA offers preserved ankle motion, improved functional results, and lower risk of adjacent joint degeneration, while providing equivalent pain relief. Historically, coronal plane deformity thresholds, such as limiting TAA to patients with less than 10–15° of malalignment, were considered necessary to ensure implant survival and stability. However, recent studies challenge these rigid criteria, demonstrating successful outcomes even in cases with deformities up to 30°, provided that appropriate osseous realignment and ligamentous stability are achieved intraoperatively. Evidence increasingly supports that residual, rather than preoperative deformity, is the critical prognostic factor influencing long-term implant success. This perspective emphasizes the importance of comprehensive preoperative planning, including assessment of limb alignment, hindfoot and subtalar joint involvement, and ligamentous balance. With adjunctive procedures for correction, modern prosthetic designs, and careful patient selection, TAA can yield stable, plantigrade, and functional ankles across a broader spectrum of deformities than previously accepted. The question “Is there a limit?” may no longer be defined by a strict degree of malalignment, but instead by the surgeon’s ability to restore alignment and stability, ensuring durable and satisfactory outcomes for patients undergoing ankle replacement. Level of evidence I; Type of study; Evaluation of results.